ANALISIS PENGARUH VARIABEL MAKRO EKONOMI GLOBAL DAN MAKRO EKONOMI DOMESTIK TERHADAP INDEKS HARGA SAHAM SEKTOR PROPERTI DAN REAL ESTATE DENGAN METODE GARCH (Periode Januari 2004-Desember 2014) - Sofyani, Nurin Widyastuti; Wahyudi, Sugeng (Diponegoro Journal of Management, 2016)
Investment in the capital market especially stocks required an analysis in order to achieve the goal of getting the maximum return with a certain risk level. Analysis at the global or domestic macroeconomic level is one of an analysis step that needed to be done. In the previous studies, there are research gaps related to the relationship of global macroeconomic variables or domestic with the movement of the stock price index property. This study aimed to analyze the factors that affect the property stock price index.            The method’s steps in this research are descriptive analysis; stationarity test; Generalized AutoRegressive Conditional Heteroscedasticity model analysis (GARCH); best model selection test (Akaike information Criterion (AIC) test, Schwarz Criterion test (SC) and significance test); classical assumption test (normality test, heteroskedasticity test, multicolinearity test and autocorrelation test); also hypothesis testing (R2 test, F test, z test) using Eviews 8 program. This study has 108 samples using monthly data from 2006-2014 for each variables.            The output of this research indicate that the GARCH (1,1) is the best model that can explain the influence of global macroeconomic variables and also domestic macroeconomic against the property stock price index. Based on the hypothesis testing results, it shows that the BI rate has a negative and significant impact on the property stock price index. Exchange rates, DJIA index, NIKKEI 225 index and world gold prices has a positive and significant impact on the property stock price index. Meanwhile, inflation, the Fed rate and world oil prices have no significant effect on the property stock price index.